ANALISIS KOMITMEN ORGANISASI, KESIAPAN SUMBERDAYA MANUSIA, INFRASTRUKTUR SERTA SISTEM INFORMASI DALAM MENERAPKAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL - Azman, Tengku (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2015)
Abstract The purpose of this study was to determine the readiness of the Government of Kepulauan Meranti indicated with commitment, human resources, facilities and information systems; to know the constraints in the implementation of Government Regulation No. 71 of 2010 concerning the Government Accounting Standards (SAP) and to determine the acceleration of the implementation of the strategic model of PP No. 71 of 2010 on Government Accounting Standards (SAP). Type of research is descriptive qualitative research. The research was conducted by taking object in Kepulauan Meranti Regional Government. The type of data used in this study is primary data and secondary data. Methods of data analysis using descriptive analysis. Based on the previous data analysis Kepulauan Meranti government readiness is indicated by the commitment, human resources, facilities and information systems can be concluded that the district government integrity is seen from the parameter set categories and human resources for preparedness, readiness and information systems infrastructure is a category quite ready . Constraints in the implementation of Government Regulation No. 71 of 2010 concerning the Government Accounting Standards (SAP), among others, to date preparation LKPD still done manually no special software, the number of HR executive in quantity is not enough, lack Bimtek or training, lack of socialization, existing facilities and infrastructure, but still not sufficient. Acceleration of the implementation of the strategic model of PP. 71 of 2010 on Government Accounting Standards (SAP), among others Accrual-Based SAP Development according to the needs, preparation of Accrual-Based SAP Technical Bulletins as needed, Human Resource Development in the Field of Government Accounting.